The Influence of Patient Sex on Outcomes Following One-Stage and Two-Stage Revision for Periprosthetic Joint Infection in Total Joint Arthroplasty - Rory W. Metcalf; Taylor Rowe; Megan Tersteeg; Malcolm E. Dombrowski; Susan Odum; Jesse E. Otero (MDPI AG, 2023)
Although females have a higher rate of primary total joint arthroplasty (TJA), males have a higher rate of revision. The literature lacks studies examining the relationship between sex and outcomes following single and two-stage exchange for periprosthetic joint infection (PJI). The purpose of this study was to examine if differences exist in outcomes following revision for chronic PJI between sexes. A retrospective review was performed on all patients with an MSIS confirmed PJI who underwent a single or two-stage exchange at our institution from January 2010 to January 2021. Patient demographics, comorbidity characteristics, and outcomes were collected and compared between males and females. The primary outcome variable was disease-free survival at 1 year following definitive revision. Multivariable logistic regression analysis was performed to determine risk factors for failure. Of the 470 patients meeting final eligibility criteria, 250 were male and 226 were female (2 males and 4 females had a joint infection of either the contralateral side or a different joint and were treated as separate records). Of the patients in the cohort, 80% of the males (200/250) and 80% of the females (181/226) were found to be disease-free at 1-year follow-up (p > 0.99). Multivariable logistic regression analysis showed that nicotine use and diabetes, but not sex, were significant predictors of failure. Our study did not find a relationship between sex and outcome of revision for PJI. Further research is required to determine whether differences exist between males and females in the expression of PJI and outcomes following treatment.